Some New Refined General Boas-Type Inequalities. (25th December 2011) - Čižmešija, A.; Pečarić, J.; Pokaz, D.
Abstract : We state and prove a new refined Boas-type inequality in a setting with a topological space and generalσ -finite and finite Borel measures. As a consequence of the result obtained, we derive a new class of Hardy- and Pólya-Knopp-type inequalities related to balls inℝ n and prove that constant factors involved in their right-hand sides are the best possible.